2010
DOI: 10.3390/md9010059
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Metabolites from a Marine-Derived Endophytic Fungus Penicillium chrysogenum QEN-24S

Abstract: Penicillium chrysogenum QEN-24S, an endophytic fungus isolated from an unidentified marine red algal species of the genus Laurencia, displayed inhibitory activity against the growth of pathogen Alternaria brassicae in dual culture test. Chemical investigation of this fungal strain resulted in the isolation of four new (1–3 and 5) and one known (4) secondary metabolites. Their structures were identified as two polyketide derivatives penicitides A and B (1 and 2), two glycerol derivatives 2-(2,4-dihydroxy-6-meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 26 publications
2
49
0
1
Order By: Relevance
“…Some examples are the new oxylipin and steroidal acetylcholinesterase inhibitors (Qiao et al, 2011); curvularin-type macrolides presenting antibacterial, antifungal and algicide properties (Dai et al, 2011), several classes of terpenes like the antimicrobial indoloterpenes (Qiao et al, 2010), sesquiterpenoids with antiplasmodial activity (Osterhage et al, 2002b), tetracyclic diterpenes (Gao et al, 2011a) and one antimicrobial monoterpene (Gao et al, 2011b cytotoxic steroids with tetrahydroxy and C-16-acetoxy groups (Gao et al, 2011c), antimicrobial and cytotoxic polyketides (Gao et al, 2011b), aromatic pentaketides of the dihydroisocoumarins class (Pontius et al, 2008a) and cytotoxic benzaldehyde derivatives (Wang et al, 2006).…”
Section: Endophytic Marine Microorganismsmentioning
confidence: 99%
“…Some examples are the new oxylipin and steroidal acetylcholinesterase inhibitors (Qiao et al, 2011); curvularin-type macrolides presenting antibacterial, antifungal and algicide properties (Dai et al, 2011), several classes of terpenes like the antimicrobial indoloterpenes (Qiao et al, 2010), sesquiterpenoids with antiplasmodial activity (Osterhage et al, 2002b), tetracyclic diterpenes (Gao et al, 2011a) and one antimicrobial monoterpene (Gao et al, 2011b cytotoxic steroids with tetrahydroxy and C-16-acetoxy groups (Gao et al, 2011c), antimicrobial and cytotoxic polyketides (Gao et al, 2011b), aromatic pentaketides of the dihydroisocoumarins class (Pontius et al, 2008a) and cytotoxic benzaldehyde derivatives (Wang et al, 2006).…”
Section: Endophytic Marine Microorganismsmentioning
confidence: 99%
“…Novel bioactive secondary metabolites from marine microbes, especially from fungi, have been lately been studied for the development of principal therapeutic molecules against various diseases (Gao et al 2011). The present study is the continuation of our recent report on the evaluation of the therapeutic potential of the endophytic fungus, C. cladosporioides isolated from the seaweed, S. wightii (Manjunath et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…14,15) Compound 1, ½ (10) revealed that the structures of these two compounds are very similar 16,17) except that, the methylene signal of C-2 at C 35.2 and the oxymethine signal of C-3 at C 70.9 in 10 was replaced by an oxymethine signal at C 69.4 and a methylene signal at C 39.2, respectively, in the 13 C NMR of 1.…”
mentioning
confidence: 99%
“…4) Several studies have found that OSMAC is a powerful technique to make available the chemical diversity of fungi. 5,6) As part of our recently initiated program to assess the chemical and biological diversity of marine-derived fungi, [7][8][9][10][11] we investigated the influence of culture conditions on metabolite production in the fungal strain Penicillium commune QSD-17, a marine-derived fungus isolated from a sediment sample collected in the South China Sea. When cultivated in liquid potato dextrose broth (PDB) medium, the fungus produced six new azaphilone derivatives as major metabolites.…”
mentioning
confidence: 99%